(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
This study was conducted to analyze the profitability of banana farming in some selected areas of Tangail district of Bangladesh during 2015. A total of 60 samples (16 small, 19 medium and 25 large farmers) were directly interviewed using a structured questionnaire for achieving the purpose. Apart from the descriptive analysis of the socio-economic variables of the selected respondents, the benefit-cost and functional profitability analysis of banana farming were also performed. The Cobb-Douglas production function was chosen to determine the effects of various inputs on the profitability of banana. The finding of cost-benefit analysis reveals that banana farming is a profitable activity in Bangladesh as the estimated cost of production was lower than the return in the selected study areas. However, the profitability differs among different farmers’ group and large farmers are more profitable in banana farming than small and medium farmers. In addition, the functional analysis identifies four inputs such as the cost of human labor, manure, fertilizer and irrigation as the significant determinants of profitability of banana farming in the study area. In this study, resource use efficiency was also measured to show the efficient resource allocation to attain the goal of profit maximization which showed that human labor, seedling, manure, fertilizer, insecticides, irrigation and bamboo has inefficient use of the resources, and farmers should limit the use of these inputs. The researcher suggested some recommendations to improve the present production situation so that banana farming could be more viable and attractive commercial enterprise. Int. J. Agril. Res. Innov. Tech. 9(2): 67-75, December 2019